Одна тень на двоих: [роман] / Т. В. Устинова - Устинова Татьяна (Первая среди лучших, 2011)
Экземпляры: ф15 (20190515) / Инвентарный номер: 194263 / Цена: / Авт.знак: У 80 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)